2011
DOI: 10.1007/s10854-011-0510-y
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and optical limiting studies of HAP and HAP@SiO2 core–shell nanoparticles

Abstract: We report the spectral and optical limiting properties of two kinds of HA P nanoparticles (pure HA P and HA P @SiO 2 core-shell nanoparticles) that were wetchemically prepared and coated with silica by means of Stober method. The size, framework substitution and silica coating formation of the resultant particles were confirmed by Transmission Electron Microscopy, X-ray diffraction, Fourier Transform Infrared Spectroscopy and Thermogravimetric analysis. The nonlinear optical limiting properties of HA P and HA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 21 publications
2
9
0
Order By: Relevance
“…HAp peaks are observed to be greatly suppressed and some peaks disappear due to the surface coating of tantalum (Ta) on HAp. Similar effects have been observed by earlier investigators [42][43][44]. Ta has smaller atomic (2.09 Å) and ionic (0.64 Å (Ta 5+ )) radii than Ca which has an atomic radius of 2.23 Å and ionic radius of 1.00 Å [45].…”
Section: Structural and Morphological Analysissupporting
confidence: 86%
See 1 more Smart Citation
“…HAp peaks are observed to be greatly suppressed and some peaks disappear due to the surface coating of tantalum (Ta) on HAp. Similar effects have been observed by earlier investigators [42][43][44]. Ta has smaller atomic (2.09 Å) and ionic (0.64 Å (Ta 5+ )) radii than Ca which has an atomic radius of 2.23 Å and ionic radius of 1.00 Å [45].…”
Section: Structural and Morphological Analysissupporting
confidence: 86%
“…This also leads to the decreased crystallinity of HAp/Ta. A Similar effect has been observed in silica, Fe 3 O 4 coated HAp core-shell nanoparticles [42,43]. In addition, the preparation of HAp/Ta by using a non-aqueous solvent in an inert atmosphere (Ar atmosphere) helps in the formation of metallic Ta around the HAp core.…”
Section: Structural and Morphological Analysissupporting
confidence: 68%
“…The increase in the value of c (3) for the Ag-CdSe hybrid PNC lm as compared to that of the pure CdSe PNC lm may be due to the SPR resulting from the doped silver metal, which largely enhances the local eld near the particle's surface. 110 Wang et al 111 also observed a dramatic increase (eight times) in the n 2 value for Ag/LiNbO 3 as compared to that in pure LiNbO 3 due to the surface plasmon interactions.…”
Section: Colloidal Chemical Synthesismentioning
confidence: 95%
“…During the phase transformation, the “hard-soft-hard” (HAP-ACP-HAP) connections disappeared and the “hard-hard” (HAPtransferred HAP-HAP) attachment began to dominate in the linear assembly with the guiding effect of glycine31. It is believed that amino acids or proteins could interact with the HAP over the thin ACP layer333435, which explains why Gly can guide HAP@ACP core-shell nanoparticles into oriented and ordered arrays.…”
mentioning
confidence: 99%